Influence of alkaline modification on selected properties of banana fiber paperbricks - Abayomi A. Akinwande (Nature Portfolio, 2021)
Abstract In a bid to develop paper bricks as alternative masonry units, unmodified banana fibers (UMBF) and alkaline (1 Molar aqueous sodium hydroxide) modified banana fibers (AMBF), fine sand, and ordinary Portland cement were blended with waste paper pulp. The fibers were introduced in varying proportions of 0, 0.5, 1.0 1.5, 2.0, and 2.5 wt% (by weight of the pulp) and curing was done for 28 and 56 days. Properties such as water and moisture absorption, compressive, flexural, and splitting tensile strengths, thermal conductivity, and specific heat capacity were appraised. The outcome of the examinations carried out revealed that water absorption rose with fiber loading while AMBF reinforced samples absorbed lesser water volume than UMBF reinforced samples; a feat occasioned by alkaline treatment of banana fiber. Moisture absorption increased with paper bricks doped with UMBF, while in the case of AMBF-paper bricks, property value was noted to depreciate with increment in AMBF proportion. Fiber loading resulted in improvement of compressive, flexural, and splitting tensile strengths and it was noted that AMBF reinforced samples performed better. The result of the thermal test showed that incorporation of UMBF led to depreciation in thermal conductivity while AMBF infusion in the bricks initiated increment in value. Opposite behaviour was observed for specific heat capacity as UMBF enhanced heat capacity while AMBF led to depreciation. Experimental trend analysis carried out indicates that curing length and alkaline modification of fiber were effective in maximizing the properties of paperbricks for masonry construction.